LABELING ASSESSMENT OF LACTOSE-FREE DAIRY PRODUCTS: rotulagem de produtos lácteos isentos de lactose: avaliação da conformidade - Emmanuela Menezes Costa,; Giovanna Cobe Vargas,; Renata Luana de Pádua Gandra,; Geralda Gillian Silva Sena, (Revista de Ciências da Saúde Nova Esperança, 2025)
The reliability of information contained in labels is crucial, especially for individuals with lactose intolerance. This study investigated the reasonableness of information on 70 labels of lactose-free milk and dairy products sold in supermarkets in the Metropolitan Region of Grande Vitória, Espírito Santo. The products were categorized into 15 groups and featured the phrases "lactose-free", "zero lactose,""0% lactose," "without lactose," or "does not contain lactose" adjacent to the product nomination. A checklist was developed containing 76 items from RDCs n° 429/2020 and IN nº 75/2020, 64 items from n° 727/2022, and 3 from n° 715/2022, from Anvisa. The items were classified as "compliant", "non-compliant", or "not applicable", and the data obtained were tabulated in Microsoft Excel® and analyzed through frequency estimation (%) and by groups. For RDC N° 429/2020, an adequacy rate of 63.1% was observed for all evaluated items, with non-compliance primarily related to the new model of nutritional information table and its constituents. Among the groups, 6 (40.0%) had a higher percentage of non-compliance regarding RDC N° 727/2022. It was also noted that none of the products complied with the requirements of this legislation. One label (1.4%) in the cheese group did not comply with RDC N° 715/2022 as it was not lactose-free despite the claim on its label. The information on labels presented some inadequacies concerning current legislation, which could compromise consumers' health and quality of life.